The UHMWPE handbook : ultra-high molecular weight polyethylene in total joint replacement - Kurtz, Steven M., 1968- (Academic Press, 2004)
This book describes the history and properties of ultra-high molecular weight polyethylene (UHMWPE) used in artificial joints. UHMWPE is currently used in 1.4 million patients around the world every year for use in the hip, knee, upper extremities and spine. It has been used in hip replacements for over 40 years. Although the use of this material is very succcessful, the lifetime of artificial joints is limited to approximately 10 years, after which the survivorship declines markedly. Recently, the orthopedic industry has developed new processing techniques (radiation crosslinking), which are expected to dramatically reduce wear and improve the longevity of hip implants beyond 10 years. A major emphasis of this book is to describe the properties of these new highly crosslinked UHMWPE materials and to review the latest clinical results. * The most up-to-date information on the properties of UHMWPE * Endorsed by Ticona - the world's leading manufacturer of UHMWPE for medical use * An enormous 'installed base' of over 1.4 million procedures each year * UHMWPE has been used by orthopedists for over 40 years, yet its properties and performance in situ are still not well understood.